The Implementation of The Poverty Reduction Policy in Malang City on The Perspective of The Grindle’s Implementation Model - Paulus Diki Takanjanji; Sumartono Sumartono; Mardiyono Mardiyono (Sekolah Pascasarjana Universitas Brawijaya, 2018)
The government of Malang City has set a policy to reduce poverty that becomes a guarantee for the poor to be prosperous. However, there has been lack of coordination, synergy, and integration of implementers, and the fact that the programs are not targeting the right people; these all have made the policy goals not achieved. Therefore, this study aims to describe and analyze the implementation of poverty reduction policies conducted by the government of Malang according to the implementation model proposed by Grindle. Data collection is done by interviews, observations, and document reviews. Data analysis technique employs the one by Miles et al. The results show that the poverty rate in Malang City has decreased. The poor are getting more prosperous. However, there are programs that are not targeted well and are not sustainable because the poor people trained are less competitive due to small capital and low production technology. In addition, the monitoring and assistance after training is unavailable, the implementers are lacking in focus on the poor or policy objectives, and there has been lack of coordination, synergy, and integrity in the implementation. In addition, the ego of the policy implementing team, the lack of control of the executive leader against subordinates, the bad management of resources,Â the lack of utilization of technology resources in the follow up of community efforts, the low allocation of the empowerment budget, and too many implementers affecting the interests of the target group have made the situation even worse. Thus, the goals are not achieved according to the plan.